2019
DOI: 10.1080/02640414.2019.1609392
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between split-step timing and leg stiffness in world-class tennis players when returning fast serves

Abstract: This study investigated split-step timing when returning serves and whether this timing is related to neuromechanical capabilities in world-class tennis players. In Experiment 1, the split-step timing of four groups of world-class players (male and female ATP/WTA seniors, and ITF juniors) was measured on court when returning serves of the same level players. The four groups initiated the split-step at a similar time, starting around the time ball-racket contact in the serve stroke and landed when early ball-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
3
10
1
Order By: Relevance
“…Specifically, large effects were observed for sprint and COD responders, moderate to large effects were observed for acceleration responders and moderate effects were observed for CMJ responders, showing all responder groups initiated an earlier movement response post-SSGs. Taken together, while the findings from this study were not conclusive, they do intimate that anticipation may be influenced by physical action capabilities, and thereby, further supports the suggestion that the timing of anticipation may be action-scaled Wilson et al, 2018;Mecheri et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Specifically, large effects were observed for sprint and COD responders, moderate to large effects were observed for acceleration responders and moderate effects were observed for CMJ responders, showing all responder groups initiated an earlier movement response post-SSGs. Taken together, while the findings from this study were not conclusive, they do intimate that anticipation may be influenced by physical action capabilities, and thereby, further supports the suggestion that the timing of anticipation may be action-scaled Wilson et al, 2018;Mecheri et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…Mecheri and colleagues (2019) concluded that increased leg stiffness may enhance servereturn performance, by affording players the option to delay their movement response and base their actions on later, more reliable information, such as ball flight. Such findings strengthen claims that action capabilities are scaled to response times and therefore, play a critical role in anticipation accuracy Witt, Linkenauger, & Wickens, 2016;Mecheri et al, 2019;Wilson et al, 2019).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In interceptive tasks, such as returning tennis serve, saving a penalty kick in soccer, or making a save in field hockey, intercepting a ball is performed under temporal and spatial constraints and requires movement preparation, execution, and adaptation in a time window that can exceed the action of an opponent and the travel time of a ball (Jackson and Mogan, 2007 ; Müller and Abernethy, 2012 ; Morris-Binelli et al, 2021 ). Three main phases during interception tasks have been proposed to contribute significantly to interception performance (Müller and Abernethy, 2012 ; Mecheri et al, 2019 ). In the first preflight phase, the movement characteristics of an opponent are perceived, allowing the observer to initiate his movement toward the interception point.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the tennis serve return, the highest variability in the upper limb movements of a server was associated with the preparation phase of the serve and the ball contact phase. Between these two phases, the vertical ball toss was identified as one of the most critical phases related to anticipation of serve type and movement initiation (Jackson and Mogan, 2007 ; Mecheri et al, 2019 ). The movements of the arm and racquet during the backswing and upswing are thought to contribute to the anticipation of ball flight direction and guide the initial movements of the returning player (Jackson and Mogan, 2007 ; Button et al, 2011 ; Navia et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%